A Female Quest in Anne Tyler’s Breathing Lessons and Ladder of Years - Shalin, Jenitta M; Reni Y.G (International Journal of Psychosocial Rehabilitation, 2020)
Anne Tyler, one of America’s most acclaimed novelists creates her own world in her writings. She has beautifully conceived and masterfully executed the emotional confusions spawned by dislocated and dysfunctional families with women at the centre of her stories. Tyler’s fiction is distinctive. Her characters are remarkable with their basic decency, essential humanity, and individual courage. Women, particularly are confronted with a difficult dilemma on how to cope under the oppressive rule, or the institution of marriage that makes them forget their dreams and goals, they once had. By taking care of the household chores, women completely forget themselves and their goals. The quest for self-identity begins at a very later stage for Tyler’s women, when they could not change things any more.